Rancang Bangun Server HAproxy Load Balancing Master to Master MySQL (Replication) Berbasis Cloud Computing - Eka Pandu Cynthia; iwan iskandar; Anwar Alfaruqi Sipayung (UIN Sumatera Utara, 2020)
At present, the development of cloud computing technology is experiencing rapid development. Also in line with the increase in the need and use of cloud computing technology itself. This rapid and high increase can cause an increase in load for the existing server so that it can result in overload on the connection path traffic. To avoid and optimize management on the server, it is necessary to share network load using various solutions available in the load balancing method. One solution is to use HAProxy software. HAProxy bridges at least 2 servers to apply load balancing and use the Round Robin scheduling algorithm. In the database management of two servers, replication Master to Master can be used by using MySQL as an existing database management media. From the results of tests conducted in this study, the HAProxy server is considered capable of handling problems compared to a single server. A replication that was tested was also considered to be a solution to bridge changes in existing data on the HAProxy server.